The Analysis Study Of Diagnosis And Surgical Management Of Phyllodes Tumor : A Comprehensive Systematic Review - Horas, Surya Martua (Program Studi Pendidikan Biologi, 2024)
Background: Phyllodes tumor (PT) is a rare form of breast tumor with a diverse range of behaviors based on pathological characteristics. It is classified into benign, borderline, and malignant types, with only those classified as borderline or malignant known to metastasize. PTs typically present as palpable breast lumps or are discovered through ultrasound examinations. Diagnosis involves core needle biopsy, mammography, ultrasound, and breast MRI. Primary treatment involves surgical excision, with adjuvant treatments reserved for borderline or malignant tumors. Methods: Following PRISMA 2020 guidelines, this systematic review focused exclusively on full-text articles published in English between 2014 and 2024. To ensure the inclusion of high-quality sources, editorial pieces and review articles were excluded unless they were accompanied by a DOI. The literature search was conducted using several reputable databases, including ScienceDirect, PubMed, and SagePub, to comprehensively gather relevant studies. Result: The study conducted a comprehensive review of over 200 publications sourced from reputable databases, including ScienceDirect, SagePub, and PubMed. Following an initial screening, eight publications were identified as warranting more in-depth analysis. Consequently, a thorough review of these selected studies was performed to ensure a detailed and rigorous evaluation. Conclusion: Phyllodes tumors, a rare fibroepithelial cancer, are typically found in women aged 45-49. They present as painless, rapidly growing masses, with malignant tumors exhibiting a higher risk of recurrence. Surgical management is crucial to achieve a negative margin, with RT being considered for malignant tumors after wide excision